EFL Undergraduate Students’ Perceptions of Online Learning Applications during the COVID-19 Outbreak - Hendrawaty, Nurmala (Universitas Pendidikan Ganesha, 2021)
The sudden outbreak of Coronavirus disease 19 or COVID-19 has affected the educational system worldwide leading to the wide world schools and universities. It makes the teaching and learning process be done through online learning. Therefore, this research focuses on EFL undergraduate students’ perceptions of the use of online learning applications during the COVID-19. There were 200 participants chosen with simple random sampling from regular class, the academic year 2019-2020, English Education Program at Universitas Indraprasta PGRI. An online questionnaire with a Likert scale was used to collect data. Then data analysis employed qualitative descriptive research to analyze two indicators: experience and comfort. The findings showed that the two indicators were in the same category (positive). It indicated that EFL undergraduate students had positive experiences and felt convenient in operating 4 out of 10 popular online learning applications. They preferred using WhatsApp Group, Email, Google Classroom, and YouTube channel during online learning. Lecturers should keep on operating the most favorable online learning applications and designing online engaging courses so that all students feel positive, enjoyable, and motivated to take online learning during the COVID-19 outbreak.